KNOWLEDGE IS POWER: HOW SUBSIDIARY CREATE KNOWLEDGE BY RELATIONAL EMBEDDEDNESS AND KNOWLEDGE SPILLOVERS - Chen, Lu-Jui (PEOPLE: International Journal of Social Sciences, 2024)
In this study, the relationship between environmental competitiveness and knowledge creation in subsidiaries is examined, suggesting that external relational embeddedness serves as a mediator and knowledge spillover acts as a moderator of this relationship. We analyzed a sample of 189 subsidiaries in Shanghai, Mainland China. The findings indicate that environmental competitiveness has a positive effect on the external embeddedness of subsidiaries. Specifically, subsidiary external relational embeddedness not only directly affects subsidiary absorptive capacity and knowledge creation but also has a fully mediating effect on this relationship. Regarding the effect of knowledge spillovers, only unconscious knowledge spillovers allow subsidiaries to expand their relational networks, increase their sources of knowledge, and notably increase their opportunities for knowledge creation. Both the theoretical and empirical implications are further discussed.